Use of neuraminidase inhibitors for rapid containment of influenza: a systematic review and meta-analysis of individual and household transmission studies - Okoli, G.N.; Otete, H.E.; Beck, C.R.; Nguyen-Van-Tam, Jonathan (Public Library of Science, 2014)
Objectives: To assess the effectiveness of neuraminidase inhibitors for use in rapid containment of influenza. Method: We conducted a systematic review and meta-analysis in accordance with the PRISMA statement. Healthcare databases and sources of grey literature were searched up to 2012 and records screened against protocol eligibility criteria. Data extraction and risk of bias assessments were performed using a piloted form. Results were synthesised narratively and we undertook meta-analyses to calculate pooled estimates of effect, statistical heterogeneity and assessed publication bias. Findings: Nine randomised controlled trials (RCTs) and eight observational studies met the inclusion criteria. Neuraminidase inhibitors provided 67 to 89% protection for individuals following prophylaxis. Meta-analysis of individual protection showed a significantly lower pooled odds of laboratory confirmed seasonal or influenza A(H1N1) pdm09 infection following oseltamivir usage compared to placebo or no therapy (n=8 studies; odds ratio (OR) 50.11; 95% confidence interval (CI)=50.06 to 0.20; p<0.001; I-2=58.7%). This result was comparable to the pooled odds ratio for individual protection with zanamivir (OR=0.23; 95% CI 0.16 to 0.35). Similar point estimates were obtained with widely overlapping 95% CIs for household protection with oseltamivir or zanamivir. We found no studies of neuraminidase inhibitors to prevent population-wide community transmission of influenza. Conclusion: Oseltamivir and zanamivir are effective for prophylaxis of individuals and households irrespective of treatment of the index case. There are no data which directly support an effect on wider community transmission.